Smart algorithm based on the optimization of SVR technique by k-NNR method for the prognosis of the open-circuit and the reversed polarity faults in a PV generator, ISSN / e-ISSN 1974-9821 / 2533-1701 - Wail Rezgui; Mouss Nadia Kenza; Mouss Leila Hayet; Mouss Mohamed Djamel (International Review on Modelling and Simulations, 2015)
This paper deals with a new smart algorithm allowing open-circuit and reversed polarity faults prognosis in photovoltaic generators. Its contribution lies on the optimization of support vector regression (SVR) technique by a k-NN regression tool (k-NNR) for undetermined outputs. To testing the performance of the proposed algorithm, we used a significant data base containing the generator functioning history, and as indicators we selected variance, standard deviation, Confidence interval, absolute and relative errors.